Hummatov, Anar - (:unkn) unknown (My University, 2026)
Anar Hummatov Hummat was born in 1973 in the Zardab District of Azerbaijan. In 1990, he graduated from Yarmammadbagi Secondary School named after Imadaddin Nasimi in the Zardab District. In the same year, he enrolled in the Faculty of Mechanics and Mathematics at Baku State University, graduating in 1995 with a degree in Mechanics and Applied Mathematics. From 1995 to 1998, he pursued postgraduate studies at the Azerbaijan Scientific Research Institute of Hydrotechnics and Land Reclamation. After successfully defending his dissertation, he was awarded the degree of Doctor of Philosophy (PhD) in Engineering by the Higher Attestation Commission under the President of the Republic of Azerbaijan in 2010. He began his academic career at the Azerbaijan University of Architecture and Construction as a Senior Laboratory Assistant in the Department of General Education Disciplines of the Faculty for International Students. Between 1998 and 2016, he served as an Assistant Lecturer, Lecturer, and Senior Lecturer on a contractual basis. Since 2016, he has been affiliated with the Department of Higher Mathematics of the Faculty of Construction Technology and Municipal Engineering. He initially worked as a contractual Senior Lecturer and, in 2020, was elected through a competitive selection process to the position of Senior Lecturer, which he currently holds. In parallel with his teaching activities, he has worked at the Laboratory of Land Reclamation of the Azerbaijan Scientific Research Institute of Hydrotechnics and Land Reclamation, serving as a Junior Researcher, Senior Researcher, and Lead Researcher on a part-time basis.